Toxicokinetics of β-Amanitin in Mice and In Vitro Drug-Drug Interaction Potential - Young Yoon Bang; Im-Sook Song; Min Seo Lee; Chang Ho Lim; Yong-Yeon Cho; Joo Young Lee; Han Chang Kang; Hye Suk Lee (MDPI AG, 2022)
The toxicokinetics of β-amanitin, a toxic bicyclic octapeptide present abundantly in Amanitaceae mushrooms, was evaluated in mice after intravenous (iv) and oral administration. The area under plasma concentration curves (AUC) following iv injection increased in proportion to doses of 0.2, 0.4, and 0.8 mg/kg. β-amanitin disappeared rapidly from plasma with a half-life of 18.3-33.6 min, and 52.3% of the iv dose was recovered as a parent form. After oral administration, the AUC again increased in proportion with doses of 2, 5, and 10 mg/kg. Absolute bioavailability was 7.3-9.4%, which resulted in 72.4% of fecal recovery from orally administered β-amanitin. Tissue-to-plasma AUC ratios of orally administered β-amanitin were the highest in the intestine and stomach. It also readily distributed to kidney > spleen > lung > liver ≈ heart. Distribution to intestines, kidneys, and the liver is in agreement with previously reported target organs after acute amatoxin poisoning. In addition, β-amanitin weakly or negligibly inhibited major cytochrome P450 and 5'-diphospho-glucuronosyltransferase activities in human liver microsomes and suppressed drug transport functions in mammalian cells that overexpress transporters, suggesting the remote drug interaction potentials caused by β-amanitin exposure.